Rioters and subversives: repression, persecution, and indigenous rights violations during the military dictatorship - Clovis Antonio Brighenti (Universidade Federal de Santa Catarina, 2020)
This article examines acts of espionage and repression on behalf of the military governments upon indigenous peoples' organizations and their supporters in the Southern Region of Brazil. Indigenous policies in the period from 1964 to 1985 went through different inquiries, such as: the Parliamentary Committees of Inquiry in the National Congress (1964, 1968, 1977); the investigation opened by Jader de Figueiredo Correia to inquire into Indigenous Protectin Agency; the dissolution of this organization and the creation of National Foundation for Indigenous People; changes in indigenous rights introduced by the 1968 Constitutional Reform; and the creation of the Indigenous Statute (Law 6001/1973). When it comes to both administrative and legal realms, such actions have brought about profound changes in the daily lives of indigenous communities. However, both government employees' involvement in economic sectors and the exploitation of natural resources in Indigenous lands have caused unprecedented violence, despite the legal support provided for indigenous peoples. The indigenous movement came to be considered "subversive" and highly dangerous to the regime. In the last decade of the dictatorial government, indigenous people were seen as internal enemies to be fought. Thus, the creation and equipment of the indigenous police were part of the routine of control exercised in the so-called "Indigenous Posts" and in the Indigenous Prisons. However, from 1974 on, they have not been alone anymore: besides congregating in indigenous gatherings, they have received the support of an important sector of the Catholic Church that has also been long attacked and spied on by the Regime.